Narrativas de mulheres com gestação de alto risco em tempos de pandemia de Covid-19: desafios para a humanização do cuidado - Silva, Mayara Ciciliotti da (2021)
The proposals to redefine prenatal and childbirth care practices in the country during the pandemic brought to light the multiple meanings of risk, highlighting the inclusion of all pregnant and postpartum women in the "risk group" for 2019 nCoV Disease and the implementation of stricter health protocols and the restriction of companions. Despite the advance in the production of scientific knowledge about labor and birth, this process enabled the preponderance of the narrative of the medical record based on clinical facts at the expense of spaces for exchange to talk about their experiences from their points of view on the processes of struggle and resistance that neither began nor ended during hospitalization. Thus, it was proposed to share the narratives of women diagnosed with high-risk pregnancy who are hospitalized in a Maternity Hospital in the city of Vitória (ES) in the context of the 2019 nCoV Disease pandemic. To this end, inspired by the methodological bet of Escrevivências coined by Conceição Evaristo, 22 women participated in the study and their stories were presented through the literary genre of short stories, bringing the outbreak of the pandemic as an analyzer of the care practices provided to women with High-Risk pregnancy in hospital. Based on this experience of meeting women and their narratives, three lines of analysis were proposed: conceptions of care and maternity; social role of the woman-mother identity; and projects, protagonisms and resistances. The results of the study indicated that the pandemic brought the chronicle of existing challenges such as gender discrimination and policies that perpetuate sexism and structural racism. Therefore, it is possible to point out the effects of the pandemic in the threat to ensure the reproductive rights of women and especially in societies in which pregnancy and birth were medicalized with risk as a key concept. Thus, it points to the importance of care practices that advocate active listening, the protagonism of women and all the actors involved, so that we do not get caught up in the chronicity of already known challenges that have not yet been overcome.